The peace movement and politics in Germany — the original ideas and self-awareness of peace advocates in both German states - Ulrich Frey (Российский журнал истории Церкви, 2023)
The article presents an attempt at historical understanding of the experience gained by a united Germany, extracted from the idea of peace, both at the state and at the public level, with its own German characteristics   —   East and West Germany. The evangelical churches in the Federal Republic of Germany and the German Democratic Republic perceived the nuclear threat as a casus confessionis  and led the fight against it.